Gender Differences in Honesty: Groups Versus Individuals - Gerd Mühlheusser; Andreas Roider; Niklas Wallmeier (Institute for the Study of Labor (IZA), 2014)
Extending the die rolling experiment of Fischbacher and Föllmi-Heusi (2013), we compare gender effects with respect to unethical behavior by individuals and by two-person groups. In contrast to individual decisions, gender matters strongly under group decisions. We find more lying in male groups and mixed groups than in female groups.
Keywords: C91; C92; J16; 330; unethical behavior; lying; group decisions; gender effects; experiment